Analisis Implementasi Projek Penguatan Profil Pelajar Pancasila dalam mengembangkan pendidikan karakter siswa sekolah dasar - Liya Lisnawati; Wahyudin Wahyudin; Jennyta Caturiasari (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
This research is motivated by the existence of a new policy in the project program to strengthen the profile of Pancasila students in character education, in practice, namely to form Indonesian students who have basic competencies and behaviors that are in accordance with Pancasila values. In order for students to have national character in accordance with Pancasila and the 1945 Constitution, the government issued a project program to strengthen Pancasila student profiles to support the implementation of character education for elementary school students. This study uses a qualitative approach and descriptive method. Data collection techniques by means of interviews, observation, and documentation studies. Data analysis techniques by means of data reduction, data presentation, drawing conclusions and verification, and conducting data validity. The results of this study are 1) school program policies to develop character education are the realization of the school's vision and mission as well as project programs to strengthen the profile of Pancasila students. 2) the process of implementing the project to strengthen the Pancasila student profile based on the Kepmendikbudristek guidelines No. 56 of 2022 Guidelines for Implementing the Curriculum. 3) the obstacles faced are in terms of the family economy and the lack of facilities from schools. 4) efforts made in dealing with obstacles, namely by evaluating consistently, making modules, annual programs, semester programs adapted to programs that will be implemented in schools.